2023
DOI: 10.1101/2023.02.06.527335
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paradoxical activation of oncogenic signaling as a cancer treatment strategy

Abstract: Cancer homeostasis depends on a balance between activated oncogenic pathways driving tumorigenesis and engagement of stress-response programs that counteract the inherent toxicity of such aberrant signaling. While inhibition of oncogenic signaling pathways has been explored extensively, there is increasing evidence that overactivation of the same pathways can also disrupt cancer homeostasis and cause lethality. We show here that inhibition of Protein Phosphatase 2A (PP2A) hyperactivates multiple oncogenic path… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…It has been shown that DTPs have increased stress levels, which suggests that challenging them with an additional stress could be lethal. We used a stress-focused compound library (agents that target proteotoxic stress, metabolic stress, oxidative stress, DNA damage stress, mitotic stress, and senolytics), 16 with the aim of identifying compounds that can be used to eradicate DTPs/DTEPs. Senescent cells share properties with DTPs, suggesting that they may share vulnerabilities.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that DTPs have increased stress levels, which suggests that challenging them with an additional stress could be lethal. We used a stress-focused compound library (agents that target proteotoxic stress, metabolic stress, oxidative stress, DNA damage stress, mitotic stress, and senolytics), 16 with the aim of identifying compounds that can be used to eradicate DTPs/DTEPs. Senescent cells share properties with DTPs, suggesting that they may share vulnerabilities.…”
Section: Resultsmentioning
confidence: 99%
“…A synthetic lethality between Wee1-like protein kinase (WEE1) inhibition and PP2A inhibition was identified in two CRC cell lines. Combination treatment of LB-100 and the WEE1 inhibitor, adavosertib, exerted a synergistic anti-proliferative effect across in vitro models of CRC, pancreatic ductal adenocarcinoma, and cholangiocarcinoma [36].…”
Section: Emerging Hallmarks Of Cancer: Senescence Drug-tolerant Persi...mentioning
confidence: 94%
“…Finally, Professor Bernards demonstrated that acquired resistance to both PP2A and WEE1 inhibitions resulted in a reduced tumourigenic phenotype. When the resistant cells were implanted into in vivo models, tumours either failed to grow or small tumours developed [36].…”
Section: Emerging Hallmarks Of Cancer: Senescence Drug-tolerant Persi...mentioning
confidence: 99%
“…More recently, Sugiura et al presented the therapeutic concept of ERKp activators [58][59][60] . Concurrently, René Bernards and colleagues described Paradoxical Intervention, signifying the simultaneous activation of mitogenic signals and the employment of stress-inducing compounds in cells with pre-existing ERK pathway-activating alterations 61,62 . Remarkably, they have demonstrated that such treatment enforces unprecedented tumor-suppressive resistance mechanisms 62 .…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, René Bernards and colleagues described Paradoxical Intervention, signifying the simultaneous activation of mitogenic signals and the employment of stress-inducing compounds in cells with pre-existing ERK pathway-activating alterations 61,62 . Remarkably, they have demonstrated that such treatment enforces unprecedented tumor-suppressive resistance mechanisms 62 . Dostoevsky once remarked, 'We all come out from Gogol's 'Overcoat," paying homage to Nikolai Gogol as the iconic predecessor of Russian literature preceding his own generation.…”
Section: Introductionmentioning
confidence: 99%